Abrupt resumption of the African Monsoon at the Younger Dryas-Holocene climatic transition - (:unkn) unknown (My University, 2007)
A high-resolution sedimentary record from Lake Masoko (Tanzania), based on pollen assemblages and magnetic susceptibility, shows that the most prominent environmental change of the last 45 000 years occurred ca 11.7 cal. ka BP, near the end of the Younger Dryas event. During this climatic transition, the Masoko catchment vegetation changed from being intolerant to a long/severe dry season to being tolerant, while the inferred lake-dynamics indicates strengthened seasonal fluctuations and/or lower levels than before. Comparison of the Masoko record with other regional palaeoclimatic data shows that evidence of this climatic transition is widespread in tropical Africa. The proposed failure of the African Monsoon during the Younger Dryas, associated with a southward position/migration of the meteorological equator in East Africa, was followed by an abrupt and lasting resumption of monsoon activity, and more pronounced migration of the Intertropical Convergence Zone (ITCZ) over the African continent. Such a reorganisation of the atmospheric circulation, equally observed across the whole tropical region (South America, East and West Asia, and Africa), could have been a strong amplifier of northern high latitude changes in temperature and precipitation across this major climatic transition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: African Research